دراسة مقاومة القص في الجوائز البيتونية المسلحة عرضياً بقضبان FRP باستخدام التحليل الاحصائي (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2019)
beams are subjected to effect of bending moment and shear strength, It is necessary to present an adequate resist to shear strength, to avoid the happening of any kind of the sudden shear failure, which often happen without a previous index. Many researches were done to improve shear strength of concrete beams or reinforcement it to resist shear. At the last time many researches have been done to use FRP fiber reinforced polymer bars, sheets and laminates: Carbon fiber reinforced polymer CFRP, Glass fiber reinforced polymer GFRP, Or  Aramid fiber reinforced polymer AFRP. this research  present many design equations which calculate shear strength of concrete beams reinforced with fiber reinforced polymer bars, suggested by previous researchers or certified by international codes. and a statistical assessment was conducted of these relationships based on experimental studies of multiple research which can be adopted to be improved and to evaluate shear strength of beams. The result of statistical analysis showed that the tow  equations is EL-Sayed and an American Code ACI440-06 are the most suitable equation to be improved in according to experimental studies. تتعرض الجوائز لتأثير عزوم انعطاف مترافقة مع قوى قص, فيتوجب تأمين مقاومة كافية لقوى القص لتجنب حدوث أي شكل من أشكال الانهيارات المفاجئة, التي ما تحدث بدون مؤشرات مسبقة, أجريت عدة دراسات لتحسين مقاومة الجوائز البيتونية أو تدعيمها على القص. كما أجريت عدة دراسات في الآونة الأخيرة لاستخدام قضبان أو شرائح أو صفائح بوليميرية مدعمة بألياف FRP : الكربونية CFRP , الزجاجية GFRP, الأراميدية AFRP. يعرض هذا البحث، عدة علاقات لحساب مقاومة القص للجوائز البيتونية المسلحة بقضبان البوليمير المقوى بالألياف، مقترحة من باحثين سابقين أو معتمدة بالكودات العالمية، أجري تقييم إحصائي لها بالاعتماد على الدراسات التجريبية لأبحاث متعددة لتحديد أفضل العلاقات توافقاً مع الدراسات التجريبية، والتي يمكن اعتمادها لتطويرها لتقييم مقاومة الجوائز للقص. أظهرت نتائج التحليل الإحصائي أن العلاقتين EL-Sayed وعلاقة الكود الأمريكي ACI440-06 أكثر ملاءمة للتطوير حسب الدراسات التجريبية.